Microbial interaction of arbuscular mycorrhizal fungi as a bioenhancer on germination, growth and Yield of Soybean (Bangladesh Journal of Botany, 2025)
The symbiosis between soybeans and Arbuscular Mycorrhiza Fungi (AMF) has drawn significant research interest due to its potential in sustainable agriculture and improved crop yields. Thus, the present study was carried out to evaluate the response of AMF as bioenhancers in case of BARI Soybean-6. Doses were 12 with 4 replications and the total number of pots was 48. The results indicated that combined application of AMF, vermicompost (VC), nitrogenous fertilizer (NF), and phosphorus (P) increased germination up to 100%, fresh root weight (0.831 g), dry root weight (0.219g), fresh shoot weight (4.522g), dry shoot weight (1.244 g), root length (13 cm), shoot length (59.75 cm), number of leaves (40.75), pod number (5.75), spore population (231.3 ± 12.0) and root colonization (30.0 ± 2.9). This combined effect of treatment T12 was found to be statistically significant in most cases.Bangladesh J. Bot. 54(1): 39-47, 2025 (March)